Improved total site heat integration incorporating pressure drop and process modifications - Chew, Kew Hong (2015)
Heat Integration (HI) has been a well-established energy conservation strategy in the industry. Total Site Heat Integration (TSHI) has received growing interest since its inception in the 90’s due to the ample energy saving potential available from TSHI implementation. This study assesses the TSHI methodology for industrial implementation and extended the TSHI methodology to (a) incorporate pressure drop, (b) maximise energy saving and (c) reduce capital cost of heat transfer area. A detailed assessment of the current TSHI methodology for industrial implementation has identified five key issues influencing the TSHI solution: (1) design, (2) operations, (3) reliability/availability/maintenance (RAM), (4) regulatory/policy and (5) economics. By considering these issues in the early stages, practical TSHI solutions can be obtained. This assessment has provided a direction for future extension of TSHI methodology from the industrial perspective. This work has also extended the TSHI methodology to consider pressure drop, one of the key design issues for Total Site (TS) due to large distances between plants. Pressure drop reduces the amount of steam that can be raised from the Site Source and changes the profile of hot utilities at the various levels. The utility circulation pumps have to be designed for a higher discharge head to overcome the frictional and elevation head loss in the distribution network. Consideration of pressure drop leads to an increase of about 4 % to both the heating and cooling utility requirements and significantly change the hot utilities profile between -75 % and +54 %. The improved methodology provides a more realistic basis for the design of central utility systems and the utility circulation pumps. The second and third extended TSHI methodologies complement the individual process analysis by bringing it within the TS context. The second methodology adapts the Plus-Minus Principle and applied it to TS. It identifies the options to maximise energy savings on site using the Total Site Profiles (TSP), the Utility Grand Composite Curve and a new set of heuristics. With the proposed process modifications, a case study performed demonstrated that a potential saving of 9 % in overall heating and 7 % in cooling utilities can be achieved. The third methodology adapts the Keep-Hot-Stream-Hot and Keep-Cold- Stream-Cold Principles to TS. Together with the TSP, the expanded TS Problem- Table-Algorithm and a comprehensive set of heuristics, the TSP is favourably changed to provide a larger temperature driving force to reduce the capital cost of the heat transfer units. The proposed modifications resulted in a modest reduction of heating and cooling utilities of between 1 % and 4 %, respectively and a more noticeable capital cost saving of about 9 %. These two methodologies enable the plant designers/engineers to pinpoint process modification efforts to improve site HI. The proposed changes to the process/streams should be assessed from feasibility, practicality and economic perspectives